Implementasi Metode Multi-Attribute Utility Theory dalam Sistem Pendukung Keputusan Rekomendasi Program Studi Perguruan Tinggi (Studi Kasus: SMAN 1 Wonoayu) - Dhia Hayyu Syahirah (Fakultas Ilmu Komputer, 2025)
The selection of a major for final-year students in senior high school that aligns with their interests, talents, and academic performance is crucial in supporting academic success while in higher education and future careers path. However, a preliminary study conducted at SMAN 1 Wonoayu revealed that only 27.66% of 88 students were confident with their major plan. This is because the consultation on the selection of major at school only pays attention to student characteristics without paying attention to students' academic grades. To address this issue, this research developed a web-based decision support system for major selection recommendation using the MAUT method that considers aspects of student interests, talents, and academic grades. The alternatives used in this study comprised 25 major, including 15 science and 10 social science study programs. The metric accuracy calculation results showed 94.23% out of 104 samples, with only 6 samples not in accordance with manual calculations.
Repository Januari 2026_Hasyim
Keywords: Pemilihan Program Studi; MAUT; SPK.